Efficacy of alogliptin, a dipeptidyl peptidase‐4 inhibitor, on glucose parameters, the activity of the advanced glycation end product (AGE) – receptor for AGE (RAGE) axis and albuminuria in Japanese type 2 diabetes. Issue 8 (November 2013) - Sakata, Koji; Hayakawa, Manabu; Yano, Yuichiro; Tamaki, Noboru; Yokota, Naoto; Eto, Takuma; Watanabe, Reiko; Hirayama, Naoteru; Matsuo, Takeshi; Kuroki, Kazuo; Sagara, Seiji; Mishima, Osamu; et al.
Abstract Background To examine the effects of alogliptin, a dipeptidyl peptidase‐4 inhibitor, on glucose parameters, the advanced glycation end product (AGE)‐receptor for AGE (RAGE) axis and albuminuria in Japanese type 2 diabetes patients. Methods Sixty‐one patients whose HbAlc ≥ 6.1% (mean age 64.7 years; 67% men; mean HbAlc 7.4%; 57% were pharmacologically treated) underwent blood and urine sampling and analysis before and after 12 weeks of treatment with alogliptin (25 mg once daily). Results Alogliptin treatment significantly reduced fasting glucose (160.3 mg/dL at baseline versus 138.0 mg/dL at 12 weeks), glycoalbumin (21.1% at baseline versus 18.9% at 12 weeks), HbAlc (7.4% at baseline versus 6.9% at 12 weeks), circulating soluble form of RAGE concentrations (847.3 pg/mL at baseline versus 791.4 pg/mL at 12 weeks) and urine albumin to creatinine ratio (31.6 mg/g Cr at baseline versus 26.5 mg/g Cr at 12 weeks), whereas 1, 5‐anhydroglucitol concentrations were significantly increased (7.5 µg/mL at baseline versus 11.6 µg/mL at 12 weeks; all P < 0.05). Circulating AGEs concentrations were reduced only in patients with baseline AGEs ≥7 U/mL (n = 33, from 8.2 U/mL to 7.2U /mL; p < 0.01) after alogliptin treatment. The treatment‐induced change of soluble form of sRAGE concentrations was associated with changes of 1, 5‐anhydroglucitol and HbAlc concentrations (rho = −0.32 and 0.29, respectively). Meanwhile, the treatment‐induced change of urine albumin to creatinine ratio was associated with a change in the fasting glucose concentration (rho = 0.25; all p < 0.05). During the intervention, alogliptin treatment was well tolerated without any hypoglycemia or side effects. Conclusion Alogliptin treatment improved the AGE–RAGE axis and reduced albuminuria in Japanese type 2 diabetes patients. Copyright © 2013 John Wiley & Sons, Ltd.